Identification of uniparental disomy following prenatal detection of Robertsonian translocations and isochromosomes. - Berend, S A (2000)
Rearrangements of the acrocentric chromosomes (Robertsonian translocations and isochromosomes) are associated with an increased risk of aneuploidy. Given this, and the large number of reported cases of uniparental disomy (UPD) associated with an acrocentric rearrangement, carriers are presumed to be at risk for UPD. However, an accurate risk estimate for UPD associated with these rearrangements is lacking. A total of 174 prenatally identified acrocentric rearrangements, including both Robertsonian translocations and isochromosomes, were studied prospectively to identify UPD for the chromosomes involved in the rearrangements. The overall goal of the study was to provide an estimate of the risk of UPD associated with nonhomologous Robertsonian translocations and homologous acrocentric rearrangements. Of the 168 nonhomologous Robertsonian translocations studied, one showed UPD for chromosome 13, providing a risk estimate of 0.6%. Four of the six homologous acrocentric rearrangements showed UPD, providing a risk estimate of 66%. These cases have also allowed delineation of the mechanisms involved in producing UPD unique to Robertsonian translocations. Given the relatively high risk for UPD in prenatally identified Robertsonian translocations and isochromosomes, UPD testing should be considered, especially for cases involving the acrocentric chromosomes 14 and 15, in which UPD is associated with adverse clinical outcomes.